Of Conflict and Concealment: The Gospel of Mark as Tragedy - Wright, Adam Z. (My University, 2015)
Perhaps since its composition, the Gospel of Mark has troubled scholarship with regard to its content and genre. In it, a number of anomalies appear: Jesus' use of secrecy, Jesus' use of the "son of man" title, how the miracles and exorcisms function with regard to plot, and why Jesus never convinces his listeners of his message. In this study, I argue that these anomalies can be explained by considering Mark's Gospel in light of the tragic genre. Mark's Gospel does not simply contain motifs or modes from tragedy; Mark's Gospel is a tragedy. Through the examination of extant Greek Tragedy and an application of Hegel's theory of tragic Kollision, this study illustrates the ways in which the plot of Mark's Gospel is built upon a tragic foundation. Kollision describes how Jesus is in conflict as the tragic hero. Conflict becomes central to this study, in which Jesus is the antagonist to the Temple and the cultural ethos it creates. This antagonism defines Jesus as the Messiah and concealed Son of God, and it produces the suffering and death common to all of tragedy. What is more, this study critically engages with several tragic theories, ranging from ancient to modern. It specifically analyzes Aristotle's Poetics-the standard description of tragic genre-and ask whether Aristotle's categories really do provide an exhaustive definition of ancient tragedy.
Keywords: conflict, concealment, Gospel of Mark, tragedy, Jesus, Messiah